PENGARUH PENGGUNAAN MEDIA CANVA TERHADAP HASIL BELAJAR IPAS SISWA MATERI GAYA DI KELAS IV SDN 3 MIJEN KALIWUNGU KUDUS: Indonesia - Nur, Veramasari; Widiyono, Aan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of using Canva media on students’ learning outcomes in Science (IPAS) on the topic of Force among fourth-grade students at SDN 3 Mijen Kaliwungu Kudus. The research employed an experimental method with a pre-experimental design, specifically the One-Group Pretest–Posttest Design. The study was conducted at SDN 3 Mijen Kaliwungu Kudus. The sample consisted of all 23 students in Grade IV. Data were collected using a multiple-choice test comprising 30 questions. Data analysis was carried out using simple linear regression analysis. The results indicated that the implementation of Canva media had a significant positive effect on improving students’ learning outcomes in Science (IPAS), particularly on the topic Force Around Us, at SDN 3 Mijen Kaliwungu Kudus. The average score increased from 66.2 in the pretest to 81.6 in the posttest. The hypothesis testing results showed that the calculated t-value (9.156) was greater than the critical t-value (1.714), leading to the rejection of H₀ and acceptance of H₁. These findings demonstrate that Canva media is effective in enhancing students’ understanding and learning motivation by providing a more engaging and interactive learning experience.